Fertility preservation outcomes may differ by cancer diagnosis - Mary Ellen Pavone; Jennifer Hirshfeld-Cytron; Angela K Lawson; Kristin Smith; Ralph Kazer; Susan Klock (Wolters Kluwer Medknow Publications, 2014)
Context : Cancer survival has improved significantly and maintaining fertility is both a major concern and an important factor for the quality of life in cancer patients. Aims : To explore differences in oocyte stimulation for fertility preservation (FP) patients based on cancer diagnosis. Settings and Deign : Between 2005 and 2011, 109 patients elected to pursue FP at a single institution. Materials and Method : In vitro fertilization (IVF) outcome variables between four cancer diagnostic groups (breast, gynecologic, lymphoma/leukemia and other) and age-matched male factor or tubal factor infertility IVF control group were compared. Statistical Analysis : ANOVA and Chi-square analyses were employed to compare variables between the groups that were normally distributed. Kruskal-Wallis with subsequent Mann-Whitney U-test were used for data that were not normally distributed. Results : Women with gynecologic malignancies were significantly older than the women in the other three groups, but tended to have a better ovarian response. Women with hematologic malignancies were most likely to have been exposed to chemotherapy and had the longest stimulations with a similar number of oocytes retrieved. The age-matched IVF controls had higher peak estradiol levels, number of oocytes obtained, and fertilization rates when compared to cancer patients with or without a history of prior chemotherapy. Conclusions : Factors including age, type of cancer and chemotherapy exposure, can influence response to ovarian stimulation. Discussing these findings with patients presenting for FP may aid in setting realistic treatment expectations.